Understanding mammary gland functioning in livestock species using in-vitro mammary epithelial cells model -An overview - Mukesh, M; Shandilya, Umesh Kumar; Sodhi, Monika; Sharma, Ankita; kapila, Neha (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Understanding the mechanisms of the development of the mammary gland can increase the efficiency of milk production, as well as improve animal health. Mammary epithelial cells (MEC) are the functional unit of the mammary gland. Although, there is a well-established MEC cell line, known as MAC-T, the use of a primary cell line is preferred because it more closely mimics an in vivo model. This review focuses on utilization of MECs as a potential in vitro model to better understand mammary gland functions in livestock species. Recently, considerable advances in three dimensional modeling of the mammary gland have been made with the used of extracellular matrix for the study of branching morphogenesis which may enable rapid advances in our understanding of mammary gland biology. Progress in the exploitation of MECs as in vitro model is more productive than ever, however further research is vital.